PENGARUH PARIWISATA HALAL TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Aisyah Kurniawati (2022)
Halal tourism is a growing tourism sector in the world. In Indonesia, halal tourism has existed since 2014. So, this study investigates the influence of tourists, star hotel room occupancy rates and star hotel workers as a proxy for halal tourism on Gross Regional Domestic Product (GDP) at constant prices per capita in 11 priority destination provinces. Halal tourism as a proxy for economic growth in Indonesia from 2014 to 2018. The data in this study is panel data consisting of secondary data. This study uses quantitative methods with panel data regression analysis techniques. This study shows that tourists, star hotel room occupancy rates and star hotel workers together have a significant effect on economic growth. Then, tourists and star hotel workers each have a significant effect on growth. Meanwhile, the occupancy rate of star hotel rooms has no significant effect on economic growth. So, the government needs to pay more attention to the halal tourism hotel sector in the form of optimizing Muslim-friendly services to increase the value of the room occupancy rate. The conclusion of this research is that the development of halal tourism in Indonesia is proven to have a positive impact on economic growth.